In-Service Needs for Knowledge & Practice and Perceived Innovative Characteristics among Frontline Officers on Integrated Pest Management Extension Campaign in Terengganu - Zanariah, Mohd Nor; Nur Iziatul Athirah, M Daud (2018)
Terengganu has been reported to have the highest infestation of Red Palm Weevil (RPW) in Malaysia since 2007. A continuous extension campaign on Integrated Pest Management (IPM) has been implemented in Terengganu since early 2017 to eradicate this RPW infestation. While past studies covered the biology aspects, infestation system and damages caused by RPW as well as IPM technical approaches; none is known about the human and technology aspects of IPM such as knowledge and practice of IPM among frontline officers and their perceived innovative characteristics on IPM. These are crucial elements to facilitate effective delivery of IPM extension campaign. Thus, the purpose of this study was to determine the in-service needs on frontline officers’ knowledge and practice and their perceived innovative characteristics towards IPM extension program on RPW. This study employed the quantitative research design with the self-administered questionnaire as the study instrument. Data collection was performed at Agricultural Offices around Terengganu in April 2018. A total of 57 frontline officers participated in this study. Reliability analyses for the study variables ranged from 0.89 to 0.97. Descriptive Analysis and Explanatory Factor Analysis were performed to describe the trend of study variable, whereas, MANOVA was used to compare the study variables by four selected background characteristics of frontline officers, specifically, age, education level, office location and participant in IPM extension campaign. About 56% of frontline officers were 43 years old and younger with low education and mostly were located at federal and state offices. More than 50% of them participated in IPM extension program to eradicate IPM more than two times. This study found that higher percentage of frontline officers expressed high (~50%) to very high need (50%) for in-service on advanced than basic IPM knowledge. In contrast, higher percentage of them expressed need (~50%) to high need (~40%) for in-service on basic than advanced skills on IPM. These frontline officers highly characterized IPM with four main characteristics, i.e. compatibility, relative advantage, simplicity and trialability. Contradictory, they less viewed IPM possessed visible and invisible observability characteristics. This study discovered that the in-service needs for knowledge, practice and perceived innovative characteristics were undifferentiated by frontline officers’ demographic background. Finally, suggestions are made for effective IPM extension campaign that include classify the IPM training content into basic and advanced IPM knowledge and practice; repackage IPM and its extension campaign to highlight all its innovative attributes with special emphasis on observability; employ Sequential Exploratory Design research method for a follow-up study.